2020
DOI: 10.1097/mcg.0000000000001410
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Full-thickness Resection Device (FTRD) for Colorectal Lesions Endoscopic Full-thickness Resection

Abstract: Background and Aims: Endoscopic full-thickness resection (eFTR) is a field of increasing interest that offers a minimally invasive resection modality for lesions that are not amenable for resection by conventional methods. Full-thickness resection device (FTRD) is a new device that was developed for a single-step eFTR using an over-the scope-clip. In this meta-analysis, we aim to assess the efficacy and safety of FTRD for eFTR of colorectal lesions. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
2
12
0
3
Order By: Relevance
“…14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73…”
Section: Current Status Of Eftr: Various Applications With Outcomesunclassified
See 3 more Smart Citations
“…14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73…”
Section: Current Status Of Eftr: Various Applications With Outcomesunclassified
“…51 R0 resection did not differ based on indication (difficult adenoma, early carcinoma, and SELs) or location (proximal, distal colon, and rectum). 52 Two meta-analyses evaluating only FTRD have shown that success of insertion to target lesion, technical success, R0 resection, total complication rates were 96.1%, 89 to 90, 78 to 82, and 8 to 10%, respectively. Major bleeding, perforation, and need for emergent surgery occurred in roughly 1% cases whereas post-polypectomy syndrome was noted in 2%.…”
Section: Current Status Of Eftr: Various Applications With Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical colectomy is associated with a low rate of residual cancer, but significant morbidity. In select patients, endoscopic full-thickness resection (EFTR) may be an option [2,3]. We report EFTR using an endoscopic sleeve (Dilumen; Lumendi) with multiple endoscopic tools.…”
mentioning
confidence: 99%